The role of gut microbiota in major depressive disorder: understanding microbiota-gut-brain axis - Lorek, Julia; Sawin, Magda; Brzozowska, Wiktoria; Grobecki, Daniel; Jabłoński, Franciszek; Jabłońska, Hanna; Jarczak, Adam; Korybski, Jakub; Szeliga, Katarzyna; Waszkiewicz, Patrycja (Journal of Education, Health and Sport, 2026)
Background: Depression is a common and complex psychiatric disorder that poses a significant burden on individuals and healthcare systems. Despite extensive research, its pathogenesis remains incompletely understood, and many patients do not respond adequately to standard treatments. The gut and brain communicate through a bidirectional pathway known as the gut-brain axis. Increasing attention has been given to the role of gut microbiota in regulating this communication, leading to the concept of the microbiota-gut-brain axis (MGBA). Aim: This review aims to synthesize current evidence on the role of gut microbiota in major depressive disorder, with emphasis on MGBA-related pathways. Materials and Methods: A literature review was conducted using PubMed and Scopus. Relevant studies addressing the relationship between gut microbiota and depression were selected. Results and Discussion: The gut microbiota influences central nervous system through several interconnected pathways, including neuronal signaling, immune modulation, regulation of the hypothalamic-pituitary-adrenal (HPA) axis, and production of bioactive metabolites. Dysbiosis may lead to increased intestinal permeability, inflammation, HPA axis dysregulation, and disturbances in neurotransmission, all of which have been associated with depressive symptoms. Conclusions: Changes within the MGBA may play a role in the pathophysiology of depression. Gut microbiota represents a promising target for future therapeutic strategies. However, further research is needed to clarify causal relationships and develop effective interventions.